The Legality of Individual Social Crowdfunding in Indonesia: Regulatory Frameworks and Legal Compliance Challenges - Hasibuan, Ali Huristak Hartawan; David Novan Setyawan; Atika Dwi Lestari; Iftitahul Ilma Nafi'a (Jurnal Ilmu Hukum Kyadiren, 2026)
This research analyses the classification and legality of social crowdfunding practices under Indonesian law through a normative approach combining statutory and conceptual methods. Social crowdfunding, as a rapidly evolving digital phenomenon, is defined as an effort to collect voluntary contributions from the public through online platforms to support social activities. The research finds that social crowdfunding is legally classified as an integral part of Money or Goods Collection activities regulated under Law No. 9 of 1961. The legality of social crowdfunding conducted by individuals is complex and conditional, depending on the fulfilment of two key factors: first, whether the activity falls within the categories of exemptions recognised by law; second, whether it is conducted in accordance with the principles of voluntariness and transparency. This research identifies a significant gap between regulations requiring formal organisational permits and the reality of individual crowdfunding, which is widely conducted through social media. These findings underscore the importance of strengthening regulations, protecting donors, and enhancing supervision mechanisms to prevent the misappropriation of funds in the social crowdfunding ecosystem.